METODE JIGSAW UNTUK MENINGKATKAN AKTIVITAS BELAJAR RAGAM GERAK TARI TRADISI SISWA KELAS VII D SMP NEGERI 1 LEDO - Sinta, Emeliana; Ismunandar, Ismunandar; Fretisari, Imma (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe problem in class VII D of SMPN 1 Ledo is the lack of student learning activities and experience in dancing because students have never received dance material and participated in dance aktivities at school or outside school. Students feel embarrassed, pay less attention to the dance material that the teacher has conveyed, students sit more, shut up and listen to the teacher's explanation, lack of confidence in dancing. This happens because of habits in learning arts and culture, especially dance learning in class. Cultural arts teachers are more dominant in explaining the theories found in dance than teaching directly to learn dance practice. This research method uses descriptive research and qualitative approaches with claas room action research through the use of the Jigsaw method in learning. Increased learning activities from cycle 1 to cycle 2 are seen from an average value of 64.05 to 86,41. The conclusion of this study is that student learning activities on the material of the variety of dance movements of tradition can be increased using theJigsaw method.Â Keywords: Jigsaw Method, Learning Activities, A variety of Traditional Dance Movements.